Air quality in the German–Czech border region: A focus on harmful fractions of PM and ultrafine particles. (December 2015) - Schladitz, Alexander; Leníček, Jan; Beneš, Ivan; Kováč, Martin; Skorkovský, Jiří; Soukup, Aleš; Jandlová, Jana; Poulain, Laurent; Plachá, Helena; Löschau, Gunter; Wiedensohler, Alfred
Abstract: A comprehensive air quality study has been carried out at two urban background sites in Annaberg-Buchholz (Germany) and Ústí nad Labem (Czech Republic) in the German–Czech border region between January 2012 and June 2014. Special attention was paid to quantify harmful fractions of particulate matter (PM) and ultrafine particle number concentration (UFP) from solid fuel combustion and vehicular traffic. Source type contributions of UFP were quantified by using the daily concentration courses of UFP and nitrogen oxide. Two different source apportionment techniques were used to quantify relative and absolute mass contributions: positive matrix factorization for total PM2.5 and elemental carbon in PM2.5 and chemical mass balance for total PM1 and organic carbon in PM1 . Contributions from solid fuel combustion strongly differed between the non-heating period (April–September) and the heating period (October–March). Major sources of solid fuel combustion in this study were wood and domestic coal combustion, while the proportion of industrial coal combustion was low (<3%). In Ústí nad Labem combustion of domestic brown coal was the most important source of organic carbon ranging from 34% to 43%. Wood combustion was an important source of organic carbon in Annaberg-Buchholz throughout the year. Heavy metals and less volatile polycyclic aromatic hydrocarbons (PAH) in the accumulation mode were related to solid fuel combustion with enhanced concentrations during the heating period. In contrast, vehicular PAH emissions were allocated to the Aitken mode. Only in Ústí nad Labem a significant contribution of photochemical new particle formation (e.g. from sulfur dioxide) to UFP of almost 50% was observed during noontime. UFPs from traffic emissions (nucleation particles) and primary emitted soot particles dominated at both sites during the rest of the day. The methodology of a combined source apportionment of UFP and PM can be adapted to other regions of the world with similar problems of atmospheric pollution to calculate the relative risk in epidemiological health studies for different sub-fractions of PM and UFP. This will enhance the meaningfulness of published relative risks in health studies based on total PM and UFP number concentrations. Highlights: Harmful contributions of ultrafine particles and PM concentration were determined. Vehicular PAH emissions were allocated to the Aitken mode. Traffic-related nucleation particles and soot particles dominate the ultrafines. Heavy metals and PAH in the accumulation mode are related to solid fuel combustion. Major sources of solid fuel combustion are soft wood and domestic coal combustion.